Comparison of Claudin 18.2 expression in primary tumors and lymph node metastases in Japanese patients with gastric adenocarcinoma - Rohde, Christoph; Yamaguchi, Rin; Mukhina, Svetlana; Sahin, Ugur; Itoh, Kyogo; Türeci, Özlem (Japanese journal of clinical oncology, 2019)
The monoclonal antibody zolbetuximab (formerly IMAB362), which is being developed as a potential treatment for gastric cancer (GC), targets Claudin 18.2 (CLDN18.2), a GC biomarker. This study aimed to determine the prevalence of CLDN18.2 in primary tumors and lymph node (LN) metastases of Japanese patients with GC. CLDN18.2 expression was investigated in tissue samples from patients with gastric adenocarcinoma archived at Kurume University Medical Center, Japan, between 2000 and 2012. Expression of CLDN18.2 in tumor samples was evaluated by immunohistochemistry using the same detection antibody (43-14A) and assay used in the FAST clinical trial (NCT01630083), a phase 2 randomized trial that compared the safety and antitumor activity of the zolbetuximab-chemotherapy combination with chemotherapy alone. Samples showing any specific staining with ≥1+ intensity were defined as CLDN18.2-positive. Of 263 samples analyzed (134 primary gastric tumors and corresponding LN metastases; 128 primary tumors only; one LN metastases only), CLDN18.2 was detected in 87% (n = 228/262) of all primary tumors and 80% (n = 108/135) of LN metastases. Moderate-to-strong CLDN18.2 expression (≥2+ membrane staining intensity in ≥40% of tumor cells [FAST eligibility criterion]) was observed in 52% (n = 135/262) of primary tumors and 45% (n = 61/135) of (LN) metastases. CLDN18.2 expression was significantly higher in GCs of the diffuse histological subtype per Lauren classification and in high grade (G3) tumors. The high prevalence of CLDN18.2 among Japanese patients with GC supports the therapeutic assessment of zolbetuximab in this population.